Save the Womanhood! Vice, urban immorality and social control in Liverpool, c. 1900-1976 - Caslin, Samantha (Liverpool University Press, 2018)
Save the Womanhood is a fascinating new history about promiscuity, prostitution and the efforts of local social purists to 'save' working-class women from themselves. The book examines how the work of the Liverpool Vigilance Association was supplemented by others, such as the Women Police Patrols, the Liverpool House of Help and the local branch of the Catholic Women's League. It argues that though these organizations helped many lost and stranded women, their work also enacted a form of moral surveillance on the streets. As such, the book uncovers how important twentieth-century anxieties about changing sexual practices, female immigration, white slavery and the rise of new consumer cultures played out at local level and with what consequences for women in Liverpool. The book also brings together a wide range of local and national sources to show that when female-run, local organizations concerned about immorality went into decline in the post-war years, it was because official institutions and local law enforcement had increasingly taken up their cause. Consequently, Save the Womanhood argues that young, working-class women who travelled through Liverpool in search of work and adventure continued to arouse moral anxiety even as the city's social purists battled to maintain their influence.